Ciclo biológico, comportamiento e importancia económica de Amblystira machalana (Heteroptera: Tingidae) en el cultivo de la yuca (Manihot esculenta Crantz) - Arias, B.; Bellotti, Anthony C. (2003)
Amblystira machalana (Black lacebug) is a new pest attacking cassava leaves. The insect was first observed causing damage to cassava in 1985 in different regions of Colombia, Venezuela and Ecuador. Several research studies were conduced at CIAT on pest behavior, and life cycle. Life cycle studies were done in the laboratory (28° C and 60-70°70 RH), using petri dishes (10 cm diameter), and infecting cassava leaves with A. machalana. Studies of the insect behavior, to determine population fluctuation were done in the field using different planting time and crops stages. In addition, observations on the pest vertical plant distribution were carried out. In order to determine the economic damage and importance, field studies were conducted by protecting plants at different periods of the crop cycle using a randomized block design (3 replication per treatment and the cassava variety Mcol 22). Results show that A. machalana has five nymphal stages with an average duration of 22,3 days from eggs to adult. Field studies indicated that pest attack can occur during both wet and dry seasons, but more likely during rainy periods. Plant distribution studies indicate that insect populations are highest on leaves of the middle and lower third of the plant, were they feed. In accordance with the varietal susceptibility yield losses can range from 8,1 to 42,7% depending on the duration of the insect attack.